Performance support at the Sport Ireland Institute - Moore, P. (The Sport and Exercise Scientist, 2019)
In this article my aim is to provide a brief overview of the approach to support work at the Sport Ireland Institute. We support around 300 athletes from around 20 Olympic and Paralympic sports. As a relatively small Institute of Sport, our team members will have several roles and no-one works exclusively with a single sport. Our current organisational structure reflects a recognition that whilst it has been administratively convenient to group staff by discipline (and therefore common interest and expertise), we work with our athletes, coaches and Performance Directors as flexible, adaptable multidisciplinary teams. Why multi-professional/multi-disciplinary teams? The answer is that human performance is complex, which means that supporting that performance requires an integrated and holistic approach. No one individual on the support team will have the full picture and there is no single "reality." Every perspective has a value and each of these can (and will) impact on the understanding and action of other members of the team. We take a post-positivistic approach to our work, which embraces complexity and places emphasis on multiple viewpoints and the meaning that we (and in particular, the athlete) make of events and interactions.